Conformations and Currents Make the Nerve Signal (Journal of Mathematical Study, 2024)
Conformation changes control the function of many proteins and thus muchof biology. But it is not always clear what conformation means: is it the distribution ofmass? Is it the distribution of permanent charge, like that on acid and base side chains?Is it the distribution of dielectric polarization? Here we point out that one of the mostimportant conformation changes in biology can be directly measured and the meaningof conformation is explored in simulations and theory. The conformation change thatunderlies the main signal of the nervous system produces a displacement current—NOT an ionic current—that has been measured. Macroscopic measurements of atomicscale currents are possible because total current (including displacement current) iseverywhere exactly the same in a one dimensional series system like a voltage clampednerve membrane, as implied by the mathematical properties of the Maxwell Amperelaw and the Kirchhoff law it implies. We use multiscale models to show how thechange of a single side chain is enough to modulate dielectric polarization and changethe speed of opening of voltage dependent channels. The idea of conformation changeis thus made concrete by experimental measurements, theory, and simulations.